From ethics of care to psychology of care: reconnecting ethics of care to contemporary moral psychology - Govrin, Aner (Frontiers in Psychology, 2014)
Moral psychology once regarded ethics of care as a promising theory. However, there is evidence to suggest that nowadays moral psychology completely ignores ethics of care’s various insights. Moreover, ethics of care’s core concepts – compassion, dependence, and the importance of early relations to moral development– are no longer considered to be relevant to the development of new theories in the field. In this paper, I will firstly discuss some of the reasons which, over recent years, have contributed to the marginalization of the role of ethics of care in moral psychology. Next, I will show that ethics of care’s most promising idea centered on the care given to an infant and the importance of that care to the development of moral thinking. In this context, I will be describing the implications of John Bowlby’s attachment theories, infant research, findings in moral psychology and neuroscience. I will argue that ethics of care needs to be radically re-thought and replaced by a psychology of care, an attachment approach to moral judgment, which would establish the centrality of the caregiver’s role in moral development. The philosophical implications of this approach to the understanding of the 'rationalists’’ and ‘intuitionists’’ debate about the true nature of moral judgment is also discussed.